A comprehensive overview of triptolide utilizing nanotechnology and its potential applications in prostate diseases - Yan, Tongyin; Wang, Yiao; Hou, Zhiyan; Song, Pan; Wang, Puze; Li, Jinze; Zheng, Jing; Lv, Dong (Frontiers in Pharmacology, 2025)
Triptolide (TPL) demonstrates a broad spectrum of biological and pharmacological activities, with its primary effects encompassing anti-inflammatory and anti-tumor properties, thereby rendering it applicable in the treatment of various diseases. However, the toxicity associated with TPL has considerably limited its clinical application. In recent years, the advancement of functional nanotechnology has created new opportunities for the application of TPL. TPL has been formulated using nanotechnology, resulting in a stable and tightly bound preparation. Regarding nanoparticle release, TPL can rapidly release the drug in acidic environments, such as tumor tissues, through pH-sensitive nanoparticles, while releasing the drug slowly under normal pH conditions. Furthermore, the surface characteristics and particle size of the carrier can be adjusted to control the drug release rate, thereby enhancing efficacy and reducing side effects. In terms of nanotargeting, active targeting achieved through surface modification can increase the concentration of the drug at the lesion site. Nanotechnology enhances the effectiveness of TPL, underscores its clinical advantages and potential, improves its disease-related performance, and offers novel strategies for disease treatment. This strategy is essential for improving therapeutic efficacy while minimizing side effects and enhancing bioavailability. Nano-TPL exhibits considerable potential for clinical application, owing to its effective targeted anti-inflammatory and anti-tumor properties, as well as its minimal toxic side effects. In this review, we present a succinct summary of the pharmacological activities and adverse effects of TPL, modifications made to its delivery system via nanotechnology, and its clinical application prospect is exemplified by prostate disease.